Mental Health Awareness For Women With Dual Roles: A Case Study Of Female Teachers In Secondary Educational Institutions In Suryalaya - Hendra Gunawan; Taufik Hermansyah; Lati Sari Dewi; Siti Amirah Makarim; Sani Haryati; Iis Susanti; Entin Aminah (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
Women who take on dual roles as professionals and homemakers are vulnerable to psychological pressure, role conflict, and mental health disorders. Female teachers in pesantren-based secondary education institutions face unique challenges due to the intersection of moral, cultural, and professional expectations. This community service initiative aimed to provide education on both the positive and negative aspects of dual roles, along with practical strategies for time management and mental health maintenance. The implementation used a participatory approach and visual media. The activity was conducted on Thursday, May 15, 2025, at secondary education institutions in Suryalaya, Tasikmalaya, and was attended by 30 female teachers. The program included interactive lectures, educational video screenings, group discussions, and collective reflection. The results of the pre–post test showed a 68% increase in participants' understanding. Evaluation indicated that 92% of participants found the activity highly beneficial, and a post-event support group was formed. This intervention effectively increased the awareness of female teachers about the importance of balancing roles and maintaining mental health.